The relationship between workload and nurse stress levels - Tjokro, Silvia Haniwijaya; Saputera, Ariawan Wangsa; Marga, Irawati (Journal of Health Management Research, 2023)
Background: Hospitals have very complex work systems and activities to continue to provide the best health services for patients. The continuity of these services is supported by various resources, one of which is a nurse. The high number of hospitalized patients with respiratory problems is a challenge for nurses in the Cempaka room. The application of SOP and the use of strict PPE is a separate stressor for nurses. Methods: This study used a study correlation design, a Cross-Sectional approach. The study population was all nurses in the Cempaka room of the hospital. X as many as 44 nurses, using the total sampling technique, The independent variable is the workload, the dependent variable is the stress level. Data retrieval using questionnaire sheets, ordinal data scales. Analysis using spearman rank corelation test with alpha 0.05. Results: The results of the study found that most respondents (59.1%) had a moderate workload, and most respondents (61.4%) had moderate stress levels. The Spearman rank corelation test showed there was a meaningful relationship between workload and nurse stress levels (p = 0.001 < 0.05 then H0 was rejected). Conclusion: The workload is so much in meeting needs, handling problems and ultimately very draining energy both physical and cognitive abilities, which has an impact on the nurse's stressor